IMPORVING PROMOTIONAL MARKETING STRATEGIES FOR OUVAL RESEARCH USING ANALYTICAL HIERARCHY PROCESS (AHP) - Bimo Widyatama; Utomo Sarjono Putro (LPPM STIE Muhammadiah Bandung, 2025)
Following the Covid-19 outbreak, Indonesia's fashion industry, like that of much of the world, has experienced substantial changes. The Covid-19 pandemic's is changing customer behavior in ways that will last for a long time. Many company have been forced to change their sales methods and adopt digital platforms as a result of COVID-19's creation of new customer trends. Following these disruptions, e-commerce became a vital lifeline for Indonesia's apparel sector. Online shopping exploded as physical stores collapsed, and sites like Tokopedia, Bukalapak and Shopee became essential for the delivery of fashion items. E-commerce has changed not only how customers purchase clothing but also how companies interact with their customers.This research looks at how the well-known Indonesian streetwear company Ouval Research, which was established in 1997, has handled these shifts in the fashion sector. The study uses qualitative research to examine the opportunities and problems brought about by the post-pandemic environment, with particular attention to changes in customer behavior, the function of e-commerce in marketing and the effects of new promotional strategies. Using Analytical Hierarchy Process to finding the best promotional marketing strategies for Ouval Research is the aim of this research, particularly in light of the digital revolution and shifting customer demands. It also offers practical suggestions for the brand to improve its standing in the competitive post-pandemic fashion industry.